Vitamin D (steroid hormone) and the nervous system diseases (literature review) - D. A. Novotnyy; N. G. Zhukova; L. Р. Shperling; V. A. Stolyarova; I. A. Zhukova; A. E. Agasheva; S. V. Shtaimets; O. A. Druzhinina (Сибирский научный медицинский журнал, 2020)
The present review aims to summarize the activities of vitamin D effects on the nervous system and to clarify a vitamin D role in brain diseases, in the pathogenesis or as a serum biomarker for the disease development and severity. Objective: correlation between chronic nervous system diseases and vitamin D level. Methods: a literature research in PubMed and in Russian electronic resources by keywords: vitamin D, brain diseases, chronic nervous system diseases. Results. Vitamin D as a neurosteroid hormone stimulates cerebral activity in both adult and embryonic brain regulates the activity of neural circuits which are responsible for locomotor, reward-dependent and emotional behavior. Patients with autism spectrum disorders, schizophrenia, Alzheimer disease, multiple sclerosis, Parkinson disease and sleep disorders have been shown to have low level of vitamin D. Discussion. Data are controversial, a further study of vitamin D hypovitaminosis significance is essential for the nervous system chronic diseases manifestation and evaluation of the vitamin D dietary supplement efficiency in patients with the nervous system pathology.